Design and Implementation of General Target Aircraft Maneuver Simulation Model Based on JSBSim - Guo Yajun, Ding Hua, Yang Dengtai, Zhou Xingdong (Editorial Office of Aero Weaponry, 2021)
In the digital simulation for the test and evaluation of the air-to-air missile, the problem of poor scalability and limited maneuver type of target aircraft model is outstanding. To resolve the above problem, the design and implementation of a six-degree-of-freedom target aircraft maneuvers simulation model is presented. Firstly, the control laws of normal overload, tangential overload and roll angle overload under different target maneuvers are designed. Then, the control models of elevator, aileron and throttle of target aircraft are designed. Finally, the implementation of target maneuver simulation model based on open source dynamic model framework of JSBSim is put forward. The target aircraft simulation model is applied to the digital simulation for the test and appraisal of an air-to-air missile, and the result shows that maneuver trajectories of target model are consistent with the expected maneuver type and parameters.